Investigating the liquidity situation after the Taliban came to power in Afghanistan - bashiri, Abdulbasit (International Journal of Economics, Business, and Entrepreneurship, 2023)
The aim of this article is to analyze and know the financial situation of Afghanistan, especially the liquidity situation of banks and people's deposits after the Taliban came to power. Liquidity is the risk to a bank's earnings and capital arising from its inability to timely meet obligations when they come due without incurring unacceptable losses. Bank management must ensure that sufficient funds are available at a reasonable cost to meet potential demands from both fund providers and borrowers. Afghanistan's banks continued to face a severe liquidity crisis during the Taliban's coming to power, with access to physical bank notes being constrained and banks facing significant liquidity challenges due to declining economic activity, a lack of trust in the banking center among Afghans, and an inability to transact internationally. In this research, we use the submissions of international organizations, talking to people in the process of receiving money from banks, and the reports of private banks to examine the liquidity situation of banks. As we have seen, after the Taliban came to power, the Afghan banks faced a lack of liquidity, and some of them even went bankrupt.